Global Health Diplomacy, "San Francisco Values," and HIV/AIDS: From the Local to the Global. - KEVANY, SEBASTIAN (My University, 2015)
Background San Francisco has a distinguished history as a cosmopolitan, progressive, and international city, including extensive associations with global health. These circumstances have contributed to new, interdisciplinary scholarship in the field of global health diplomacy (GHD). In the present review, we describe the evolution and history of GHD at the practical and theoretical levels within the San Francisco medical community, trace related associations between the local and the global, and propose a range of potential opportunities for further development of this dynamic field. Methods We provide a historical overview of the development of the “San Francisco Model” of collaborative, community-owned HIV/AIDS treatment and care programs as pioneered under the “Ward 86” paradigm of the 1980s. We traced the expansion and evolution of this model to the national level under the Ryan White Care Act, and internationally via the President's Emergency Plan for AIDS Relief. In parallel, we describe the evolution of global health diplomacy practices, from the local to the global, including the integration of GHD principles into intervention design to ensure social, political, and cultural acceptability and sensitivity. Results Global health programs, as informed by lessons learned from the San Francisco Model, are increasingly aligned with diplomatic principles and practices. This awareness has aided implementation, allowed policymakers to pursue related and progressive social and humanitarian issues in conjunction with medical responses, and elevated global health to the realm of “high politics.” Conclusions In the 21st century, the integration between diplomatic, medical, and global health practices will continue under “smart global health” and GHD paradigms. These approaches will enhance intervention cost-effectiveness by addressing and optimizing, in tandem with each other, a wide range of (health and non-health) foreign policy, diplomatic, security, and economic priorities in a synergistic manner—without sacrificing health outcomes.
PUBLISHED
Keywords: diplomacy; global health; HIV/AIDS; international relations; San Francisco